2013
DOI: 10.1016/j.neuron.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Peptide Release Mediates Interpopulation Crosstalk between Neurosecretory and Preautonomic Networks

Abstract: SUMMARY Although communication between neurons is considered a function of the synapse, neurons also release neurotransmitter from their dendrites. We found that dendritic transmitter release coordinates activity across distinct neuronal populations to generate integrative homeostatic responses. We show that activity-dependent vasopressin release from hypothalamic neuroendocrine neurons in the paraventricular nucleus stimulates neighboring (~100 μm soma-to-soma) presympathetic neurons, resulting in a sympathoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
161
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 54 publications
(98 reference statements)
12
161
0
3
Order By: Relevance
“…Furthermore, Badoer et al (2003) showed that glutamatergic inputs into the PVN play an important role in the renal nerve response to elevations in osmolality. More recently, Son et al (2013) have demonstrated that an acute osmotic challenge increased RSNA, which was attenuated by the antagonism of V1a receptors within the PVN, supporting the concept that local, dendritic release of vasopressin is another relevant signal regulating sympathoexcitatory outflow from the PVN.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, Badoer et al (2003) showed that glutamatergic inputs into the PVN play an important role in the renal nerve response to elevations in osmolality. More recently, Son et al (2013) have demonstrated that an acute osmotic challenge increased RSNA, which was attenuated by the antagonism of V1a receptors within the PVN, supporting the concept that local, dendritic release of vasopressin is another relevant signal regulating sympathoexcitatory outflow from the PVN.…”
mentioning
confidence: 66%
“…Furthermore, Badoer et al (2003) showed that glutamatergic inputs into the PVN play an important role in the renal nerve response to elevations in osmolality. More recently, Son et al (2013) have demonstrated that an acute osmotic challenge increased RSNA, which was attenuated by the antagonism of V1a receptors within the PVN, supporting the concept that local, dendritic release of vasopressin is another relevant signal regulating sympathoexcitatory outflow from the PVN.In the last decades, adenosine triphosphate (ATP) has been recognized as an important neurotransmitter involved in many physiological and pathological mechanisms, besides its wellknown role as an intracellular energy source. ATP actions as a neurotransmitter are mediated via P2 receptor activation, which are divided into two classes: P2Y and P2X.…”
mentioning
confidence: 79%
“…Also, we have shown that during exposure of rats to air-jet stress, selective blockade of central VP receptors do not affect the response of the hypothalamo-pituitary axis as judged by the concentration of blood corticosterone (Stojičić et al, 2008), suggesting that VP released into the portal circulation during air-jet stress does not modulate ACTH release into the blood stream. Nonetheless, physiological stimuli know to increase VP release into the blood stream, such as hyperosmotic challenge, have been reported to increase intranuclear release of VP (Son et al, 2013) and that its role is to coordinate the optimal firing rate of the whole population of magnocellular neurons (Gouzènes et al, 1998), and also to activate pre-sympathetic neurons in the parvocellular division of PVN. This inter-neural cross-talk has been shown to involve V1aRs in PVN (Son et al, 2013), supporting the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, physiological stimuli know to increase VP release into the blood stream, such as hyperosmotic challenge, have been reported to increase intranuclear release of VP (Son et al, 2013) and that its role is to coordinate the optimal firing rate of the whole population of magnocellular neurons (Gouzènes et al, 1998), and also to activate pre-sympathetic neurons in the parvocellular division of PVN. This inter-neural cross-talk has been shown to involve V1aRs in PVN (Son et al, 2013), supporting the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation